Method for enhancing carbon dioxide fixation by a heterojunction-aerobic bacteria hybrid system

CN122979372APending Publication Date: 2026-10-27GUANGDONG INST OF ECO ENVIRONMENT & SOIL SCI
0 Cites 0 Cited by

Patent Information

Application Number
CN202510459030.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-04-14
Publication Date
2026-10-27

Smart Images

  • Figure CN122979372A_ABST
    Figure CN122979372A_ABST
Patent Text Reader

Abstract

The present application belongs to the technical field of non-metallic semiconductor nanomaterials and the field of microbial carbon dioxide fixation, and particularly relates to a method for enhancing carbon dioxide fixation by a heterojunction-aerobic bacteria hybrid system. Specifically, the method combines two-dimensional semiconductor heterojunctions with microorganisms, generates photo-generated electrons by illuminating the heterojunction semiconductor material, and conducts the generated photo-generated electrons into the bacteria through the electron mediator neutral red to participate in the internal carbon fixation cycle of the bacteria and promote the fixation of carbon dioxide. The method is simple, fast and environmentally friendly. The heterojunction material prepared has low toxicity, can better separate photo-generated electrons and holes, better transfer photo-generated electrons and has many other advantages. At the same time, the method can improve the efficiency of carbon dioxide fixation of bacteria under visible light and aerobic conditions, and has a broad application prospect.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the fields of non-metallic semiconductor nanomaterials technology and microbial carbon dioxide fixation, and particularly relates to a method for enhancing carbon dioxide fixation using a heterojunction-aerobic bacteria hybrid system. Technical Background

[0002] Fossil fuels, primarily coal, oil, and natural gas, are the foundation of economic and social development. However, with human industrialization, the continuous use of fossil fuels has led to the emission of large amounts of greenhouse gases into the atmosphere. Since modern times, the concentration of carbon dioxide in the atmosphere has been steadily increasing, causing a series of environmental problems such as global warming. Microorganisms are major drivers and participants in the Earth's element cycle. They can fix carbon dioxide and reduce the concentration of greenhouse gases in the atmosphere through various pathways, including photosynthesis, electron transport chains, and their own carbon-fixing enzymes. Moreover, microorganisms can produce various high-value-added chemicals while fixing carbon. Photocatalytic carbon fixation utilizes photocatalysts to generate photogenerated electrons and holes using light energy. Under certain conditions, these electrons and holes can convert carbon dioxide into chemicals through redox reactions, completing the conversion of light energy into chemical energy.

[0003] Photocatalysis-microbial hybrid systems integrate the advantages of both and have seen rapid development in recent years. These systems utilize solar energy to excite semiconductor materials, generating photoelectrons that provide energy and reducing power to microbial cells, promoting CBB and WLP cycles within the microorganisms and driving efficient carbon fixation and product synthesis. This system exhibits high energy conversion efficiency and can specifically synthesize high-value-added chemicals, showing broad application prospects. Currently, scientists both domestically and internationally have developed various semiconductor-microbial hybrid systems. However, the semiconductor materials used in these systems generally have low utilization rates of visible light, while visible light constitutes the largest proportion of sunlight, making it difficult for existing materials to effectively utilize visible light for photoexcitation. Furthermore, most of the microorganisms used are anaerobic, requiring demanding growth conditions, resulting in high production costs and insufficient stability of the catalytic system, hindering practical production applications. Therefore, researching a semiconductor-microbial hybrid system based on heterojunction semiconductor materials for carbon dioxide fixation is of great significance in this field. Summary of the Invention

[0004] In view of this, the object of the present invention is to provide a method for enhancing carbon dioxide fixation using a heterojunction-aerobic bacteria hybrid system.

[0005] To achieve the above objectives, the present invention adopts the following technical solution:

[0006] A method for enhancing carbon dioxide fixation using a heterojunction-aerobic bacteria hybrid system is proposed. This method utilizes a two-dimensional semiconductor heterojunction combined with microorganisms. Photogenerated electrons are generated by irradiating the heterojunction semiconductor material. These photogenerated electrons are conducted into the bacteria through the neutral red electron mediator and participate in the internal carbon fixation cycle of the bacteria, thereby promoting carbon dioxide fixation.

[0007] The two-dimensional semiconductor heterojunction is a black phosphorus nanosheet, and the microorganism is an aerobic microorganism.

[0008] specific:

[0009] Step 1: Obtain black phosphorus nanosheets from bulk black phosphorus material using a liquid phase exfoliation method;

[0010] Step 2: Urea is calcined in a muffle furnace to obtain graphitic carbon nitride material. The material is then soaked in a mixed solution of concentrated nitric acid and concentrated sulfuric acid, and then washed with water to obtain porous graphitic carbon nitride material. The obtained porous graphitic carbon nitride material is then used to obtain graphitic carbon nitride nanosheets by liquid phase exfoliation.

[0011] Step 3: Mix black phosphorus nanosheets and graphitic carbon nitride nanosheets, and obtain heterojunction semiconductor materials by water bath ultrasound.

[0012] Step 4: Inoculate Cupriavidus necator into nutrient broth medium for expansion culture, centrifuge, and then transfer to photosynthetic medium for further culture to obtain bacterial culture.

[0013] Step 5: Add heterojunction material, cysteine, and neutral red to the bacterial culture to obtain a heterojunction semiconductor-microbial hybrid system, and then carry out light and constant temperature culture to fix carbon dioxide.

[0014] The liquid phase exfoliation method in step one involves dispersing the blocky black phosphorus material into oxygen-free water and then ultrasonically processing it with an ultrasonic crusher to obtain black phosphorus nanosheets with a size of approximately 100-200 nm.

[0015] In step two, the muffle furnace calcination temperature is 545-555℃, the volume ratio of concentrated sulfuric acid to concentrated nitric acid is 1:1, the soaking time in acid is 2-2.5h, after soaking, it is washed with water until neutral, and then dispersed in oxygen-free water, ultrasonically treated with an ultrasonic disruptor, and liquid phase exfoliation is performed to obtain graphitic carbon nitride nanosheets with a nanosheet size of 100-200nm.

[0016] In step three, the concentration ratio of black phosphorus to graphite phase carbon nitride is 1:4, and the ultrasonic bath time is 2 hours.

[0017] In step four, *Ralstonia solanacearum* is inoculated into nutrient broth and cultured at 30-31°C and 150-170 rpm for 24-26 hours. Then, it is centrifuged at 5000-8000 rpm for 5-10 minutes. After centrifugation, it is transferred to photosynthetic medium and cultured at 30°C and 150-170 rpm for 24-26 hours. After culturing, its OD200 is increased using photosynthetic medium. 600 Dilute to 0.2 and set aside the resulting bacterial solution for later use.

[0018] The composition of the nutrient broth culture medium is as follows:

[0019]

[0020] The composition of the photosynthetic culture medium is as follows:

[0021]

[0022] In step five, the heterojunction material, cysteine, and neutral red were added to the bacterial culture to obtain a culture system. The system was cultured at 220 rpm, 30°C, and a pH range of 6-8 for 30 minutes to obtain a heterojunction semiconductor-microbial hybrid system. Then, the system was further cultured under a light intensity of 5 mW / cm². 2 The culture was carried out under light and constant temperature at 30℃ and 160 rpm for carbon dioxide fixation. The final concentration of heterojunction material in the culture system was 1-3 μg / mL; the mass fraction of cysteine ​​in the system was 0.01-0.05%; and the final concentration of neutral red was 5-20 mM.

[0023] The light source is an LED lamp.

[0024] Compared with existing technologies, the beneficial effects of this invention are:

[0025] The advantages of this invention are that it is simple, fast, and environmentally friendly; the prepared heterojunction material has low toxicity, can better separate photogenerated electrons and holes, and can better transfer photogenerated electrons, etc.; at the same time, this method can improve the efficiency of bacteria in fixing carbon dioxide under visible light and aerobic conditions, and has broad application prospects.

[0026] The method for enhancing carbon dioxide fixation using a heterojunction semiconductor-microorganism hybrid system provided by this invention features a simple semiconductor heterojunction fabrication process, low cost, low biotoxicity of the materials, and improved utilization of visible light by the hybrid system. Furthermore, this system significantly improves carbon fixation efficiency, requires no anaerobic or high-temperature environment, and exhibits high system stability.

[0027] Experimental results show that when the material concentration is 2 μg / mL, the cysteine ​​mass fraction is 0.02%, the neutral red concentration is 10 Mm, and the light intensity is 5 mW / cm², the optimal concentration for the experiment is 5 μg / mL. 2The carbon fixation effect was optimal during this period, with a 104.80% increase compared to pure bacteria, and a photosynthetic efficiency of 4.55%. Attached Figure Description

[0028] Figure 1 Atomic force microscopy images of black phosphorus nanosheets (BP) and graphitic carbon nitride (CN) nanosheets prepared in the examples of this invention;

[0029] Figure 2 The X-ray diffraction patterns of the black phosphorus nanosheets, graphitic carbon nitride nanosheets, and heterojunction materials (BP / CN) prepared in the examples of this invention are shown below.

[0030] Figure 3 This is a high-angle circular dark-field scanning transmission electron microscope image of the heterojunction material prepared in the example of the present invention;

[0031] Figure 4 The X-ray photoelectron spectra of black phosphorus nanosheets, graphitic carbon nitride nanosheets, and heterojunction materials prepared in the examples of this invention are shown.

[0032] Figure 5 The image shows the ultraviolet-visible-infrared absorption spectrum of the heterojunction material prepared in the example of this invention.

[0033] Figure 6 The image shows a scanning electron microscope image of the bacteria (C. ne) and the hybrid system (C. ne-BP / CN) in the example of this invention.

[0034] Figure 7 The values ​​represent the changes in bacterial activity under the influence of different concentrations of heterojunction materials in the examples of this invention.

[0035] Figure 8 This represents the numerical value of the change in the carbon dioxide fixation capacity of bacteria under the influence of light intensity in the examples of this invention;

[0036] Figure 9 This represents the numerical value of the change in the carbon dioxide fixation capacity of bacteria under the influence of neutral red (NR) concentration in the examples of this invention;

[0037] Figure 10 This represents the numerical value of the change in the carbon dioxide fixation capacity of bacteria under the influence of cysteine ​​(Cys) concentration in the examples of this invention;

[0038] Figure 11 This represents the numerical value of the change in the carbon dioxide fixation capacity of bacteria under the influence of the material (BP / CN) concentration in the examples of this invention;

[0039] Figure 12 This represents the numerical value of the carbon fixation capacity of bacteria under optimal conditions in the examples of this invention. Specific implementation methods

[0040] The technical solutions of the present invention will be clearly and completely described below with reference to the accompanying drawings in the embodiments of the present invention. Example 1

[0041] Methods to enhance carbon dioxide fixation include the following steps:

[0042] Step 1: The bulk black phosphorus was broken into small black phosphorus nanosheets (BP) using a liquid-phase exfoliation method, with a size of approximately 109 nm and a concentration of 120 μg / mL (see [link to article]). Figure 1 , Figure 2 and Figure 4 ).

[0043] Among them, the surface of blocky black phosphorus is relatively rough, its color is dark gray, and it has a metallic luster.

[0044] Step 2: Urea was calcined in a muffle furnace at 550℃ for 3 hours to obtain graphitic carbon nitride material. The graphitic carbon nitride was then immersed in a mixed solution of concentrated nitric acid (approximately 68% by mass) and concentrated sulfuric acid (≥98% by volume) at a 1:1 volume ratio for 2 hours. After immersion, it was washed with water until the pH reached 7, yielding porous graphitic carbon nitride material. The porous graphitic carbon nitride was then broken into small nanosheets using a liquid-phase exfoliation method to obtain graphitic carbon nitride nanosheets (CN). The obtained graphitic carbon nitride nanosheets (CN) had a size of approximately 136 nm and a concentration of 323 μg / mL (see [link to relevant documentation]). Figure 1 , Figure 2 and Figure 4 ).

[0045] Step 3: Mix the black phosphorus nanosheets and graphitic carbon nitride nanosheets obtained above at a concentration ratio of 1:4, and then perform ultrasonication in a water bath for 2 hours to obtain a heterojunction semiconductor material (BP / CN). Figure 2 , Figure 3 , Figure 4 and Figure 5 );

[0046] Step 4: Under aseptic conditions, *Ralstonia solanacearum* was inoculated into sterilized nutrient broth medium and cultured at 30°C and 160 rpm for 24 hours. The activated cells were collected by centrifugation at 5000 rpm for 5 minutes and then transferred to photosynthetic medium for further culture to obtain a bacterial suspension. The OD value was then adjusted. 600 =0.2 (see Figure 6 );

[0047] The composition of the nutrient broth culture medium is as follows:

[0048]

[0049] The composition of the photosynthetic culture medium is as follows:

[0050]

[0051]

[0052] Step 5: Add the obtained heterojunction material, cysteine, and neutral red to the bacterial culture. The final concentration of the heterojunction material in the bacterial culture is 2 μg / mL, the mass fraction of cysteine ​​is 0.02%, and the final concentration of neutral red is 10 mM. Incubate at 30℃ and 220 rpm for 30 min to obtain the heterojunction semiconductor-microbial hybrid system (BP / CN) (see [link to relevant documentation]). Figure 6 ).

[0053] LED lights were used to simulate sunlight, with the light intensity adjusted to 5 mW / cm². 2 A 12-hour light / 12-hour dark cycle was used to simulate the solar photocycle. The hybrid system was cultured at 30°C and 160 rpm for carbon dioxide fixation.

[0054] In step five above, carbon dioxide is fixed in the bacterial culture under different conditions, including heterojunction material (BP / CN), cysteine, neutral red, light intensity, and optimal conditions for the bacterial culture. The carbon fixation effect is then tested. Specifically:

[0055] Toxicity experiments involved adjusting the OD of the bacterial culture medium after photosynthetic culture. 600 =0.5, conduct light cultivation, use LED lights to simulate sunlight, and adjust the light intensity to 5mW / cm. 2 A 12-hour light / 12-hour dark cycle was used to simulate the solar photocycle. BP / CN heterojunction material at concentrations of 0, 5, 10, 15, and 20 μg / mL was added, and after 48 hours of incubation, the bacterial culture was collected, and the OD was measured. 600 Value as an activity indicator (see) Figure 7 ).

[0056] To investigate the optimal light intensity, the OD of the bacterial culture in the photosynthetic medium was adjusted. 600 =0.2, and cultured under light, using LED lights to simulate sunlight, with a 12h light / 12h dark cycle to simulate a solar photoperiod, at 30℃ and 160rpm for 48h. With fixed BP / CN concentration of 4μg / mL, Cys mass fraction of 0.02%, and NR concentration of 20μM, different light intensities (0, 2.5, 5, 7.5, 10mW / cm²) were used. 2 The culture was carried out. After 48 hours of culture, the PHB content in the bacterial culture was measured (see...). Figure 8 ).

[0057] To investigate the optimal NR (noise, radix, and ion exchange rate) experiment, the bacterial culture in the photosynthetic medium was adjusted to control OD (dose, ion exchange rate, and ion exchange rate). 600 =0.2, and cultured under light, using LED lights to simulate sunlight, with a 12h light / 12h dark cycle to simulate a solar photoperiod, at 30℃ and 160rpm for 48h. The BP / CN concentration was fixed at 4μg / mL, the Cys mass fraction at 0.02%, and the light intensity at 5mW / cm². 2 Different NR concentrations (5, 10, 20, 30, 40 μM) were used for culturing. The PHB content in the bacterial culture was measured after 48 hours of incubation (see [reference]). Figure 9 ).

[0058] To investigate the optimal Cys mass fraction, the OD of the bacterial culture in the photosynthetic medium was adjusted. 600 =0.2, and cultured under light, using LED lights to simulate sunlight, with a 12h light / 12h dark cycle to simulate a solar photoperiod, at 30℃ and 160rpm for 48h. The BP / CN concentration was fixed at 4μg / mL, the NR concentration at 20μM, and the light intensity at 5mW / cm². 2 Different Cys mass fractions (0.01%, 0.02%, 0.03%, 0.05%, and 0.1%) were used for culturing. The PHB content in the bacterial culture was measured after 48 hours of incubation (see [reference]). Figure 10 ).

[0059] To investigate the optimal BP / CN concentration, the OD of the bacterial culture in the photosynthetic medium was adjusted. 600 =0.2, and cultured under light, using LED lights to simulate sunlight, with a 12h light / 12h dark cycle to simulate sunlight, at 30℃ and 160rpm for 48h. Cys mass fraction was fixed at 0.02%, NR concentration at 20μM, and light intensity at 5mW / cm². 2 Different BP / CN concentrations (1, 2, 4, 6, 8, 10 μg / mL) were used for culturing. The PHB content in the bacterial culture was measured after 48 hours of incubation (see [reference]). Figure 11 ).

[0060] Experiments were conducted to investigate the effects of various substances at their optimal concentrations on bacterial carbon fixation. The bacterial culture medium was cultured in photosynthetic medium, and the OD values ​​were adjusted... 600 =0.2, and cultured under light, using LED lights to simulate sunlight, with a 12h light / 12h dark cycle to simulate a solar photoperiod, at 30℃ and 160rpm for 48h. The optimal BP / CN concentration was 4μg / mL, NR concentration was 20μM, and light intensity was 5mW / cm². 2The Cys mass fraction was 0.02%. Five groups of experiments were conducted: Group 1 was cultured under light only without BP / CN, NR, or Cys; Group 2 was cultured under light with NR but without BP / CN; Group 3 was cultured under light with BP / CN and Cys but without NR; Group 4 was cultured under light with NR, Cys, and BP / CN but without light; and Group 5 was cultured under light with BP / CN, NR, and Cys. All conditions were optimal, and the culture time was 48 hours. After culture, the PHB content in the bacterial culture was measured (see [link to experimental data]). Figure 12 ).

[0061] 2) Carbon fixation effect test: Bacteria containing heterojunction material, cysteine, and neutral red under different conditions were compared with bacteria without heterojunction material, cysteine, and neutral red as control samples to compare carbon dioxide fixation effects. After 48 hours of light / dark incubation, bacteria were collected, and the content of poly-β-hydroxybutyrate (PHB), the final product of bacterial carbon dioxide fixation, was determined by GC-MS to compare carbon fixation effects and calculate quantum efficiency (QE) (see [reference]). Figure 7-12 ).

[0062] Depend on Figure 1 It is known that the average size of the synthesized black phosphorus nanosheets (BP) is 109 nm; the average size of the graphitic carbon nitride (CN) is 136 nm.

[0063] Depend on Figure 2 It can be seen that the heterojunction material (BP / CN) contains characteristic peaks of both graphitic carbon nitride and black phosphorus, indicating that the synthesized material is a two-way composite material and the heterojunction was successfully synthesized.

[0064] Depend on Figure 3 It can be seen that graphite-phase carbon nitride materials do not have obvious lattice fringes; black phosphorus materials have obvious lattice fringes and the 0.262 lattice space corresponds to the 040 plane of black phosphorus.

[0065] Depend on Figure 4 It can be seen that by comparing the N1s and C1s spectra of CN and the heterojunction material (BP / CN), no new peaks appear in the heterojunction material spectrum, indicating that no chemical reaction has occurred in the material; by comparing the P2p spectra of BP and BP / CN, a new peak appears at 132.85 eV in the heterojunction material, indicating the formation of PN coordination bonds.

[0066] Depend on Figure 5 It can be seen that black phosphorus materials have the highest absorption in the visible light region, while graphitic carbon nitride materials have the lowest absorption in the visible light region; heterojunction materials can significantly improve light absorption performance and enhance the absorption of materials in the visible light region.

[0067] Depend on Figure 6It can be seen that compared with pure bacteria (C.ne), the bacteria after the addition of materials (C.ne-BP / CN) have more particulate matter, indicating that the heterojunction material and bacteria form a hybrid system.

[0068] Depend on Figure 7 It can be seen that when the material concentration is higher than 15 μg / mL, it has a significant impact on bacterial growth.

[0069] Depend on Figure 8-12 It can be seen that when the light intensity is 5mW / cm 2 Under conditions of 0.02% cysteine ​​(Cys) mass fraction, 10 μM neutral red (NR) concentration, and 2 μg / mL heterojunction (BP / CN) concentration, the bacterial carbon fixation capacity to produce poly-β-hydroxybutyric acid (PHB) was increased by 104.80%. The quantum efficiency of bacterial carbon fixation was calculated to be 4.55% using the following method.

[0070] The calculation method is as follows:

[0071]

[0072] C PHB =PHB concentration

[0073] V = Total volume of reaction

[0074] φ ph cm -2 s -1 = Photon flux

[0075] A = Illumination area

[0076] t = light reaction time

[0077] N A = Avogadro's constant.

Claims

1. A method for enhancing carbon dioxide fixation using a heterojunction-aerobic bacteria hybrid system, characterized in that: By combining two-dimensional semiconductor heterojunctions with microorganisms, photogenerated electrons are generated by irradiating the heterojunction semiconductor material. These photogenerated electrons enter the bacteria through the neutral red electron medium and participate in the internal carbon fixation cycle of the bacteria, promoting the fixation of carbon dioxide.

2. The method for enhancing carbon dioxide fixation according to claim 1, characterized in that: The two-dimensional semiconductor heterojunction is a black phosphorus nanosheet, and the microorganism is an aerobic microorganism.

3. The method for enhancing carbon dioxide fixation according to claim 1 or 2, characterized in that: Step 1: Obtain black phosphorus nanosheets from bulk black phosphorus material using a liquid phase exfoliation method; Step 2: Urea is calcined in a muffle furnace to obtain graphitic carbon nitride material. The material is then soaked in a mixed solution of concentrated nitric acid and concentrated sulfuric acid, and then washed with water to obtain porous graphitic carbon nitride material. The obtained porous graphitic carbon nitride material is then used to obtain graphitic carbon nitride nanosheets by liquid phase exfoliation. Step 3: Mix black phosphorus nanosheets and graphitic carbon nitride nanosheets, and obtain heterojunction semiconductor materials by water bath ultrasound. Step 4: Inoculate Cupriavidus necator into nutrient broth medium for expansion culture, centrifuge, and then transfer to photosynthetic medium for further culture to obtain bacterial culture. Step 5: Add heterojunction material, cysteine, and neutral red to the bacterial culture to obtain a heterojunction semiconductor-microbial hybrid system, and then carry out light and constant temperature culture to fix carbon dioxide.

4. The method for enhancing carbon dioxide fixation according to claim 3, characterized in that: The liquid phase exfoliation method in step one involves dispersing the blocky black phosphorus material into oxygen-free water and then ultrasonically processing it with an ultrasonic crusher to obtain black phosphorus nanosheets with a size of approximately 100-200 nm.

5. The method for enhancing carbon dioxide fixation according to claim 3, characterized in that: In step two, the muffle furnace calcination temperature is 545-555℃, the volume ratio of concentrated sulfuric acid to concentrated nitric acid is 1:1, the soaking time in acid is 2-2.5h, after soaking, it is washed with water until neutral, and then dispersed in oxygen-free water, ultrasonically treated with an ultrasonic disruptor, and liquid phase exfoliation is performed to obtain graphitic carbon nitride nanosheets with a nanosheet size of 100-200nm.

6. The method for enhancing carbon dioxide fixation according to claim 3, characterized in that: In step three, the concentration ratio of black phosphorus to graphite phase carbon nitride is 1:4, and the ultrasonic bath time is 2 hours.

7. The method for enhancing carbon dioxide fixation according to claim 3, characterized in that: In step four, *Ralstonia solanacearum* is inoculated into nutrient broth and cultured at 30-31°C and 150-170 rpm for 24-26 hours. Then, it is centrifuged at 5000-8000 rpm for 5-10 minutes. After centrifugation, it is transferred to photosynthetic medium and cultured at 30°C and 150-170 rpm for 24-26 hours. After culturing, its OD200 is increased using photosynthetic medium. 600 Dilute to 0.2 and set aside the resulting bacterial solution for later use.

8. The method for enhancing carbon dioxide fixation according to claim 3, characterized in that: In step five, the heterojunction material, cysteine, and neutral red obtained above are added to the bacterial culture to obtain a culture system. The system is then cultured at 220 rpm, 30°C, and a pH range of 6-8 for 30 minutes to obtain a heterojunction semiconductor-microbial hybrid system. This system is then further cultured under light intensity of 2.5-7.5 mW / cm². 2 The culture was carried out under light and constant temperature at 30℃ and 160 rpm for carbon dioxide fixation. The final concentration of heterojunction material in the culture system was 1-3 μg / mL; the mass fraction of cysteine ​​in the system was 0.01-0.05%; and the final concentration of neutral red was 5-20 mM.